2011
DOI: 10.1021/jo201411t
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiazoles with Tunable Electron-Withdrawing Strength and Reverse Polarity: A Route to Triphenylamine-Based Chromophores with Enhanced Two-Photon Absorption

Abstract: A series of dipolar and octupolar triphenylamine-derived dyes containing a benzothiazole positioned in the matched or mismatched fashion have been designed and synthesized via palladium-catalyzed Sonogashira cross-coupling reactions. Linear and nonlinear optical properties of the designed molecules were tuned by an additional electron-withdrawing group (EWG) and by changing the relative positions of the donor and acceptor substituents on the heterocyclic ring. This allowed us to examine the effect of positiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 113 publications
(85 reference statements)
4
97
0
1
Order By: Relevance
“…In both series, F F decreases upon branching, implying increased non-radiative pathways, but is maintained to relatively high values similar to those found for other TPA-based tri-podal molecules. 21,30,31 It is worth noting that F F for the tri-podal molecules remains relatively high even in solvents of high polarity such as acetone and acetonitrile ( Table 2). Fig.…”
Section: 3145mentioning
confidence: 99%
“…In both series, F F decreases upon branching, implying increased non-radiative pathways, but is maintained to relatively high values similar to those found for other TPA-based tri-podal molecules. 21,30,31 It is worth noting that F F for the tri-podal molecules remains relatively high even in solvents of high polarity such as acetone and acetonitrile ( Table 2). Fig.…”
Section: 3145mentioning
confidence: 99%
“…5,[8][9][10][11][12] Also, the nonlinear optical response in p-conjugated organic semiconductors attracts great interest in two-photon excited photoluminescence microscopy, [13][14][15] photodynamic therapy, 16 three-dimensional data storage, 17 microfabrication, 18 optical power limiting 19 and frequency up-converted lasing. [20][21][22] Previously, an enhanced two-photon absorption (2PA) cross-section has been demonstrated in structurally engineered oligomers [23][24][25][26][27] and molecules having elongated p-conjugation. 28, 29 Yet, frequency up-converted lasers, which have attracted increasing scientific and technological interest, 30 have not been demonstrated in fluorescent oligomers except dendrimers, 31 conjugated polymers, 20,21 donor-acceptor type organic molecules 22,32 and various dyes.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction and design of molecules with large first hyperpolarizability have received much attention, many strategies of enhancing NLO property are explored by increasing the strength of donor and acceptor, expanding the length of π conjugation, twisting π-electron systems, increasing push-pull effects, doping metal into organic compounds etc. [3,[20][21][22][23][24][25][26][27][28]; in which, endohedral fullerenes as an important strategy arouse our interest owing to π-electron-conjugated systems along with charge delocalization [29,30]. Our group has investigated the effect of different positions of Sc 2 S on the interaction energy and the nonlinear optical properties, it indicated that the change of Sc 2 S positions have significant influence on the first hyperpolarizability [31].…”
Section: Introductionmentioning
confidence: 99%